1, 4‐Iron Migration for Expedient Allene Annulations through Iron‐Catalyzed C−H/N−H/C−O/C−H Functionalizations. (30th May 2018) - Mo, Jiayu; Müller, Thomas; Oliveira, João C. A.; Ackermann, Lutz
Abstract: C−H activation bears great potential for enabling sustainable molecular syntheses in a step‐ and atom‐economical manner, with major advances having been realized with precious 4d and 5d transition metals. In contrast, we employed earth abundant, nontoxic iron catalysts for versatile allene annulations through a unique C−H/N−H/C−O/C−H functionalization sequence. The powerful iron catalysis occurred under external‐oxidant‐free conditions even at room temperature, while detailed mechanistic studies revealed an unprecedented 1, 4‐iron migration regime for facile C−H activations.